Răspuns :
a) ([tex] \frac{3}{1} [/tex]+[tex] \frac{1}{2} [/tex])·([tex] \frac{5}{11} [/tex]+[tex] \frac{1}{7} [/tex])·([tex] \frac{4}{1} [/tex]+[tex] \frac{3}{2} [/tex])=[tex] \frac{6+1}{2} [/tex]·[tex] \frac{35+11}{77} [/tex]·[tex] \frac{8+3}{2} [/tex]=[tex] \frac{7}{2} [/tex]·[tex] \frac{46}{77} [/tex]·[tex] \frac{11}{2} [/tex]=[tex] \frac{23}{2} [/tex]
b) 28=2²·7
56=2³·7
c.m.m.m.c=2³·7=8·7=56 (elemente comune si necomune la puterea cea mai mare)
[tex] \frac{7}{45} [/tex]·([tex] \frac{27}{28} [/tex]-[tex] \frac{9}{56} [/tex])=[tex] \frac{7}{45} [/tex]·[tex] \frac{54-9}{56} [/tex]=[tex] \frac{7}{45} [/tex]·[tex] \frac{45}{56} [/tex]=[tex] \frac{1}{8} [/tex]
c)([tex] \frac{5}{1} [/tex]-[tex] \frac{2}{3} [/tex])·([tex] \frac{7}{13} [/tex]-[tex] \frac{4}{26} [/tex])·([tex] \frac{7}{11} [/tex]-[tex] \frac{1}{2} [/tex])=[tex] \frac{15-2}{3} [/tex]·[tex] \frac{14-4}{26} [/tex]·[tex] \frac{14-11}{22} [/tex]=[tex] \frac{13}{3} [/tex]·[tex] \frac{10}{26} [/tex]·[tex] \frac{3}{22} [/tex]=[tex] \frac{5}{22} [/tex]
d)[tex] \frac{5*3+5}{3} [/tex]·([tex] \frac{3*5+2}{5} [/tex]+[tex] \frac{2*15+1}{15} [/tex] - [tex] \frac{3*3+1}{3} [/tex] )=[tex] \frac{20}{3} [/tex]·([tex] \frac{17}{5} [/tex] + [tex] \frac{31}{15} [/tex] - [tex] \frac{10}{3} [/tex])=[tex] \frac{20}{3} [/tex]·[tex] \frac{51+31-50}{15} [/tex]=[tex] \frac{20}{3} [/tex]·[tex] \frac{32}{15} [/tex]=[tex] \frac{128}{9} [/tex]
e) ([tex] \frac{13}{4} [/tex]+[tex] \frac{9}{7} [/tex]-[tex] \frac{45}{28} [/tex])·[tex] \frac{56}{41} [/tex]=[tex] \frac{91+36-45}{28} [/tex]·[tex] \frac{56}{41} [/tex]=[tex] \frac{82}{28} [/tex]·[tex] \frac{56}{41} [/tex]=4
f) [tex] \frac{30}{7} [/tex]·([tex] \frac{16}{5} [/tex]+[tex] \frac{106}{15} [/tex]-[tex] \frac{7}{3} [/tex])=[tex] \frac{30}{7} [/tex]·([tex] \frac{48+106-35}{15} [/tex]=[tex] \frac{30}{7} [/tex]·[tex] \frac{119}{15} [/tex]=34
b) 28=2²·7
56=2³·7
c.m.m.m.c=2³·7=8·7=56 (elemente comune si necomune la puterea cea mai mare)
[tex] \frac{7}{45} [/tex]·([tex] \frac{27}{28} [/tex]-[tex] \frac{9}{56} [/tex])=[tex] \frac{7}{45} [/tex]·[tex] \frac{54-9}{56} [/tex]=[tex] \frac{7}{45} [/tex]·[tex] \frac{45}{56} [/tex]=[tex] \frac{1}{8} [/tex]
c)([tex] \frac{5}{1} [/tex]-[tex] \frac{2}{3} [/tex])·([tex] \frac{7}{13} [/tex]-[tex] \frac{4}{26} [/tex])·([tex] \frac{7}{11} [/tex]-[tex] \frac{1}{2} [/tex])=[tex] \frac{15-2}{3} [/tex]·[tex] \frac{14-4}{26} [/tex]·[tex] \frac{14-11}{22} [/tex]=[tex] \frac{13}{3} [/tex]·[tex] \frac{10}{26} [/tex]·[tex] \frac{3}{22} [/tex]=[tex] \frac{5}{22} [/tex]
d)[tex] \frac{5*3+5}{3} [/tex]·([tex] \frac{3*5+2}{5} [/tex]+[tex] \frac{2*15+1}{15} [/tex] - [tex] \frac{3*3+1}{3} [/tex] )=[tex] \frac{20}{3} [/tex]·([tex] \frac{17}{5} [/tex] + [tex] \frac{31}{15} [/tex] - [tex] \frac{10}{3} [/tex])=[tex] \frac{20}{3} [/tex]·[tex] \frac{51+31-50}{15} [/tex]=[tex] \frac{20}{3} [/tex]·[tex] \frac{32}{15} [/tex]=[tex] \frac{128}{9} [/tex]
e) ([tex] \frac{13}{4} [/tex]+[tex] \frac{9}{7} [/tex]-[tex] \frac{45}{28} [/tex])·[tex] \frac{56}{41} [/tex]=[tex] \frac{91+36-45}{28} [/tex]·[tex] \frac{56}{41} [/tex]=[tex] \frac{82}{28} [/tex]·[tex] \frac{56}{41} [/tex]=4
f) [tex] \frac{30}{7} [/tex]·([tex] \frac{16}{5} [/tex]+[tex] \frac{106}{15} [/tex]-[tex] \frac{7}{3} [/tex])=[tex] \frac{30}{7} [/tex]·([tex] \frac{48+106-35}{15} [/tex]=[tex] \frac{30}{7} [/tex]·[tex] \frac{119}{15} [/tex]=34